Optimizing roller design to improve web strain uniformity in roll-to-roll process - Kang, Yousung; Jeon, Yongho; Ji, Hongkyu; Kwon, Sin; Kim, Ga Eul; Lee, Moon G. (Applied Sciences (Switzerland), 2020)
In this work, we investigated the compensation of strain deviation in the machine direction of a web in the roll-to-roll process. As flexible devices have become popular, many researchers have begun to study roll-to-roll processes for the mass-production of flexible devices at low cost. In the continuous roll-to-roll process, an electronic circuit pattern is printed on the web while the web is transferring. Due to tension and Poisson’s ratio, a non-uniform strain distribution can occur in the web. This strain distribution occurs mainly at the center of the web and causes a register error in the machine direction. In this work, we designed a roller to minimize the strain deviation. The design of the compensation roller was optimized using the design of experiments (DOE) methodology and analysis of variance (ANOVA), and the compensation performance was verified through experiments and simulations. According to the results of a comparative experiment conducted to confirm the correcting performance of the optimized roller, the strain deviation in the machine direction decreased by approximately 48% with the proposed roller compared to that of the conventional roller.
Keywords: Design of experiment; Roll-to-roll process; Strain deviation; Web deformation